Perlindungan Hak-Hak Konstitusional Masyarakat Adat di Kabupaten Boalemo dalam Penerapan Sanksi Adat - Lisnawaty W Badu; Julisa Aprilia Kaluku; Abas Kaluku (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
Problems with indigenous people in Boalemo district, Gorontalo Province often occur, especially the issues about the imposement of costumary sanctions. Imposing costumary sanctions without clear relugations will absolutely cause legal consequences in the future. Eventhough constitutional rights for indigenous people is already granted by the government as stated In article 18B paragraph (2), and Article 28 I paragraph (3) of The 1945 Constitution Of Republic Indonesia. This regulation is a mandate from the state and given to the regions. This regulation is oftenly referred when discussing the existence and rights of indigenous peoples and become a crutial issues when it comes to the implementation of the protection of the constitutional rights for indigenous peoples in Boalemo district Gorontalo Province. Therefore, This research aims to analyze the Legal standing for indigenous people and constitutional rights for costumary sanctions in Boalemo district Gorontalo Province. This normative research utilized secondary data as resourch and used statute approach and case approach. The results of the study discover that the costumary law and the imposement of costumary sanctions are still mantained and implemented in Indonesia. Government should more concern about constitutional rights compliance for indigenous people. However, the imposement of customary sanctions are not regulated in a regional regulation. So the constitutional rights which should become the spirit for regional autonomy to provide justice in a judiciary are only resolved by way of deliberation, This can not give the satisfaction for some parties.